2020
DOI: 10.1002/cbf.3509
|View full text |Cite
|
Sign up to set email alerts
|

LncRNA DLEU2 promotes tumour growth by sponging miR‐337‐3p in human osteosarcoma

Abstract: According to statistics, abnormal regulation of lncRNAs pivotally influences multiple malignant tumours. DLEU2, as one of these lncRNAs, is detected to be related to growth and development of tumours. The molecular mechanisms of DLEU2 in osteosarcoma, however, are still unknown. QRT-PCR was adopted to analyse the correlations of clinicopathological features and prognosis of osteosarcoma cases with DLEU2. The influences of DLEU2 on cell migration and viability were evaluated independently by experiments in vitr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 21 publications
0
17
0
Order By: Relevance
“…Its high expression was significantly associated with the pathological grading and TNM stage of GC patients. This result is consistent with previous research reports that also used RT-qPCR to detect the expression pattern of DLEU2 in other types of tumor tissues and cell lines.DLEU2 also is found to be highly expressed in other types of tumors, such as non-small cell lung cancer [23], glioma [24], esophageal cancer [25,26], osteosarcoma [27], and hepatocellular carcinoma [28,29] tissues and cell lines. Furthermore, we used siRNA and pcDNA3.1 plasmid transfection to knock down and exogenously express DLEU2 in GC cells respectively, and found that knockdown of DLEU2 inhibited the proliferation of AGS and MKN-45 cells, and induced cell apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…Its high expression was significantly associated with the pathological grading and TNM stage of GC patients. This result is consistent with previous research reports that also used RT-qPCR to detect the expression pattern of DLEU2 in other types of tumor tissues and cell lines.DLEU2 also is found to be highly expressed in other types of tumors, such as non-small cell lung cancer [23], glioma [24], esophageal cancer [25,26], osteosarcoma [27], and hepatocellular carcinoma [28,29] tissues and cell lines. Furthermore, we used siRNA and pcDNA3.1 plasmid transfection to knock down and exogenously express DLEU2 in GC cells respectively, and found that knockdown of DLEU2 inhibited the proliferation of AGS and MKN-45 cells, and induced cell apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…44 The function of LncRNA DLEU2 in suppressing tumorigenesis and progression was reported recently, including esophageal cancer, 45 hepatocellular carcinoma, 46 pancreatic cancer, 47 laryngeal squamous cell carcinoma 48 and osteosarcoma. 49 On the contrary, some reports suggested that a pro-oncogenic role of DLEU2 in cancers, such as clear cell renal cell carcinoma. 50 These studies suggested that DLEU2 might show different functions in different cancer types due to the tissue specificity.…”
mentioning
confidence: 99%
“…Herein, we screened 6 osteosarcoma-related genes by lncRNA microarray, MALAT1, HCG9, FAM99A, FAM87B, DLEU2, and C8orf49. MALAT1 and DLEU2 have been shown to promote osteosarcoma progression in previous studies [ 31 , 32 ]. FAM99A, FAM87B, and C8orf49 have not been reported in osteosarcoma studies and are rarely reported in other cancers.…”
Section: Discussionmentioning
confidence: 99%